Increasing Awareness of the Property Management Minor at MacEwan University Using Social Media, Pop-Up Booths and Student Testimonials - Sgambaro, Claudia; Durante, Kailey; Morrison, Sean; Vemula, Sid; Porter, Reese (MacEwan University Student eJournal, 2023)
The following research report responds to the need for market research expressed by the community partner in understanding why enrollment in the Property Management minor is low at MacEwan University, and how the numbers can be increased.